Food risk perceptions by different consumer groups in Germany - Jutta Roosen; Silke Thiele; Kristin Hansen (Kiel University, Department of Food Economics and Consumption Studies, 2004)
This paper presents an analysis of the changing food risk perceptions of German consumers over the period 1992 to 2002. We analyse the respondents' general risk attitudes and their specific perceptions of food risks. Using cluster analysis we generate a typology of four consumer types. One group is worried about natural food risks, the second does not worry about any types of food risks, the third is concerned about technical food risks and the fourth is concerned about all food risks. A multinomial logit analysis identifies factors that describe the classification of households in this grouping. General risk attitudes and knowledge about food risk are significant variables in the explanation.
Keywords: C24; D12; D18; 330; cluster analysis; food safety; multinomial logit; risk perceptions; risk typology